Analisis Deskriptif Service Marketing Mix Bengkel Roda Dua Suzuki Magetan - Veny Ari Sejati; Nunik Hariyani (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2018)
In general, small-beginner workshops only apply traditional marketing and run as simple as possible. Problems arise as a result of the management of the marketing management of the workshop owner who is unable to answer the demands of the customer, causing loss of customers. The formulation of the problem in this study is how the integrated marketing services of the Suzuki Magetan workshop? this research is expected to be able to develop knowledge in the field of marketing communications, especially integrated marketing services, as well as providing knowledge to business startups to be used as a reference and help increase the number of customers. Customer is an asset that determines the company's growth and development. This type of research is qualitative descriptive, because it examines the integrated service marketing of a service company and uses qualitative descriptive research methods. Data collection techniques are complete participatory observation, unstructured interviews and documentation to obtain supplementary data. The purpose of this research are to improve the ability of researchers in the field of marketing communication, to be a means for researchers to publish the results of research in national scientific journals, initiating research road maps for researchers.